10.52931/icirpe2019 Positioning Academicians in Waste Management Response - Paula Dewanti ,I Made Bali Merta Yasa,I Kadek Mardianta (International Conference on Industrial Revolution for Polytechnic Education, 2019)
In 2017, population of Indonesia is estimated to reach almost 262 million people who are dominated by productive age in which approximately 30% are in Higher Education. Data released by the Ministry of Technology and Higher Education Research (Kemenristekdikti), mentioned that number of universities in Indonesia as of February 15, 2018 is 4586, which is accumulation of 400 public universities and 4186 private colleges. Community Service, in Indonesia, is one of the main pillars in the Tri Dharma of Higher Education. Accordance to the Law No. 12 of 2012, Article 1 Paragraph 9, Tridharma Perguruan Tinggi defined as Higher Education obligation to committedly perform education, research and community service, as unabridged. As one pillars of Tridharma Perguruan Tinggi, Community Service must be carried out by lecturers in Higher Education, unified along with education and research within a certain period of time simultaneously and inseparably. Considering these, come to a thought of how academician can be of any help in waste management response. Sampling Bali as one of tourist destination in Indonesia, that recently is being highlighted by one of international media, where invasion of the volume of plastic waste is gradually widespread and increasing, this study focuses on Information System as a strategy that can be taken as consideration to assist with waste management process with an output of application of Waste Management Information System.